Дослідження оптичних властивостей шаруватих кристалів Tl1-xIn1-xSixSe2 - Кажукаускас, Вайдотас; Мирончук, Галина; Замуруєва, Оксана; Парасюк, Олег; Шаварова, Ганна; Богданюк, Микола; Kazhukauskas, Vajdotas; Mуronchuk, Galyna; Zamurueva, Oksana; Parasyuk, Oleg; Shavarova, Anna; Bogdanyuk, Nicholas (Східноєвропейський національний університет імені Лесі Українки, 2013)
У нашій роботі розглянуто закономірності зміни оптичних спектрів поглинання в кристалах твердих розчинів Tl1-xIn1-xSixSe2 (х=0,1; 0,2) з температурою. Оцінено ширину забороненої зони при непрямих gi E і прямих gd E дозволених переходах. Розраховано енергію Урбаха та параметр крутизни краю оптичного поглинання досліджуваних монокристалів Tl1-xIn1-xSixSe2 за різних температур.; From the study of optical absorption spectra of layered Tl1-xIn1-xSixSe2 solid solutions (х=0.1; 0.2) the band energy gap for direct gi E and undirect gd E allowed transitions, the Urbach energy and steepness parameter at 100-300 K have been estimated. The increase of SiSe2 content leads to the increase of donor centers (In3+ ions are submitted by Sі4+ ions) and acceptors ( Tl V ) concentrations and favors the increase of the ionicity bonding degree, decrease of lattice parameters and, as a result, to the enhancement of gi E and gd E . The Urbach energy increases with temperature and varies within 48-58 meV for х=0.1 and 90-96 meV for х=0.2. The increase of Urbach energy with x may be explained by the increase of the concentration of structural defects and unstoichiometricity. The temperature dependences of steepness parameter (from 0.179 at 100K to 0.445 at 300K for х=0.1 and from 0.096 at 100K to 0.269 at 300K for х=0.2) are related to the contribution of structural defects due to heterovalent ions substitution and layered structure and of electron-phonon interaction to the forming of absorption edge.
The Study of Optical Properties of Layered Crystals Tl1-xIn1-xSixSe2
Keywords: шарувата кристалічна структура; енергія Урбаха; параметр крутизни; chalcogenide crystals; layered crystal structure; optical properties; Urbach energy